Strategic Intermediation in Corporate Asset Markets: A Qualitative Literature Review on the Role of Non-Venture Private Equity Firms - Ria Wulandari; Mohammad Chaidir (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review explores the strategic role of non-venture private equity (PE) firms as intermediaries in corporate asset markets. Distinct from venture capitalists, these PE firms specialize in acquiring, restructuring, and reallocating mature corporate assets, thereby enhancing market efficiency and value creation. By synthesizing recent studies, this review highlights how non-venture PE firms facilitate resource redeployment, drive operational improvements, and influence corporate governance. Comparative analysis reveals their unique ability to exploit inefficiencies through carve-outs, platform building, and targeted acquisitions. The review also examines emerging ESG considerations and critiques regarding short-termism and stakeholder impact. While the literature acknowledges the transformative role of these firms, it also identifies limitations in theoretical integration and empirical coverage. This study contributes to a deeper understanding of how non-venture PE firms shape firm boundaries, market structures, and the evolving logic of strategic intermediation.